Kinetic analysis of novel multisubstrate analogue inhibitors of thymidine phosphorylase. - Balzarini, J; Degrève, B; Esteban-Gamboa, A; Esnouf, R; De Clercq, E; Engelborghs, Y; Camarasa, M; Pérez-Pérez, M (2000)
A kinetic analysis was performed for the novel 1-(8-phosphonooctyl)-6-amino-5-bromouracil and 1-(8-phosphonooctyl)-7-deazaxanthine inhibitors of Escherichia coli thymidine (dThd) phosphorylase (TPase). The structure of the compounds was rationally designed based on the available crystal structure coordinates of bacterial TPase. These inhibitors reversibly inhibited TPase. Kinetic analysis revealed that the compounds inhibited TPase in a purely competitive or mixed fashion not only when dThd, but also when inorganic phosphate (Pi), was used as the variable substrate. In contrast, the free bases 6-amino-5-bromouracil and 7-deazaxanthine behaved as non-competitive inhibitors of the enzyme in the presence of variable Pi concentrations while being competitive or mixed with respect to thymine as the natural substrate. Our kinetic data thus revealed that the novel 1-(8-phosphonooctyl)pyrimidine/purine derivatives are able to function as multisubstrate inhibitors of TPase, interfering at two different sites (dThd(Thy)- and phosphate-binding site) of the enzyme. To our knowledge, the described compounds represent the first type of such multisubstrate analogue inhibitors of TPase; they should be considered as lead compounds for the development of mechanistically novel type of TPase inhibitors.